Cardioprotective Effect of Novel Matrix Metalloproteinase Inhibitors - Gömöri, Kamilla (Int J Mol Sci, 2020)
Background: We recently developed novel matrix metalloproteinase-2 (MMP-2) inhibitor small molecules for cardioprotection against ischemia/reperfusion injury and validated their efficacy in ischemia/reperfusion injury in cardiac myocytes. The aim of the present study was to test our lead compounds for cardioprotection in vivo in a rat model of acute myocardial infarction (AMI) in the presence or absence of hypercholesterolemia, one of the major comorbidities affecting cardioprotection. Methods: Normocholesterolemic adult male Wistar rats were subjected to 30 min of coronary occlusion followed by 120 min of reperfusion to induce AMI. MMP inhibitors (MMPI)-1154 and -1260 at 0.3, 1, and 3 µmol/kg, MMPI-1248 at 1, 3, and 10 µmol/kg were administered at the 25th min of ischemia intravenously. In separate groups, hypercholesterolemia was induced by a 12-week diet (2% cholesterol, 0.25% cholic acid), then the rats were subjected to the same AMI protocol and single doses of the MMPIs that showed the most efficacy in normocholesterolemic animals were tested in the hypercholesterolemic animals. Infarct size/area at risk was assessed at the end of reperfusion in all groups by standard Evans blue and 2,3,5-triphenyltetrazolium chloride (TTC) staining, and myocardial microvascular obstruction (MVO) was determined by thioflavine-S staining. Results: MMPI-1154 at 1 µmol/kg, MMPI-1260 at 3 µmol/kg and ischemic preconditioning (IPC) as the positive control reduced infarct size significantly; however, this effect was not seen in hypercholesterolemic animals. MVO in hypercholesterolemic animals decreased by IPC only. Conclusions: This is the first demonstration that MMPI-1154 and MMPI-1260 showed a dose-dependent infarct size reduction in an in vivo rat AMI model; however, single doses that showed the most efficacy in normocholesterolemic animals were abolished by hypercholesterolemia. The further development of these promising cardioprotective MMPIs should be continued with different dose ranges in the study of hypercholesterolemia and other comorbidities.